Characterization Of Selective TRPM8 Ligands And Their Structure Activity Response (S.A.R) Relationship - Muhammad Azhar Sherkheli; Angela K. Vogt-Eisele; Daniel Bura; Leopoldo R. Beltrán Márques; Günter Gisselmann; Hanns Hatt (Journal of Pharmacy & Pharmaceutical Sciences, 2010)
PURPOSE: Transient receptor potential melastatin-8 (TRPM8) is an ion channel expressed extensively in sensory nerves, human prostate and overexpressed in a variety of cancers including prostate, breast, lung, colon and skin melanomas. It is activated by innoxious cooling and chemical stimuli. TRPM8 activation by cooling or chemical agonists is reported to induce profound analgesia in neuropathic pain conditions. Known TRPM8 agonists like menthol and icilin cross-activate other thermo-TRP channels like TRPV3 and TRPA1 and mutually inhibit TRPM8. This limits the usefulness of menthol and icilin as TRPM8 ligands. Consequently, the identification of selective and potent ligands for TRPM8 is of high relevance both in basic research and for therapeutic applications. In the present investigation, a group of menthol derivates was characterized. These ligands are selective and potent agonists of TRPM8. Interestingly they do not activate other thermo-TRPs like TRPA1, TRPV1, TRPV2, TRPV3 and TRPV4. These ion channels are also nociceptors and target of many inflammatory mediators. METHODS: Investigations were performed in a recombinant system: Xenopus oocytes microinjected with cRNA of gene of interest were superfused with the test substances after initial responses of known standard agonists. Evoked currents were measured by two-electrode voltage clamp technique. RESULTS: The newly characterized ligands possess an up to six-fold higher potency (EC50 in low µM) and an up to two-fold increase in efficacy compared to the parent compound menthol. In addition, it is found that chemical derivatives of menthol like CPS-368, CPS-369, CPS-125, WS-5 and WS-12 are the most selective ligands for TRPM8. The enhanced activity and selectivity seems to be conferred by hexacyclic ring structure present in all ligands as substances like WS-23 which lack this functional group activate TRPM8 with much lower potency (EC50 in mM) and those with pentacyclcic ring structure (furanone compounds) are totally inactive. CONCLUSION: The new substances activate TRPM8 with a higher potency, efficacy and specificity than menthol and will thus be of importance for the development of pharmacological agents suitable for treatment and diagnosis of certain cancers and as analgesics.